Metal-based engineered nanoparticles in the drinking water treatment systems: a critical review - Serrão Sousa, Vânia (2021)
The emergence of nanotechnologically-enabled materials, compounds or products inevitably leads to engineered nanoparticles (ENPs) released into surface waters. ENPs have already been detected in wastewater streams, drinking water sources and even in tap water at concentrations in the ng/L and mu g/L range, making the latter a potential route for humans. The presence of ENPs in raw waters raises concerns over the possibility that ENPs might pose a hazard to the quality and security of drinking water and whether drinking water treatment plants (DWTPs) are prepared to handle this problem. Therefore, it is essential to critically evaluate if ENPs can be effectively removed through water treatment processes to control environmental and human health risks associated with their release. This review includes a summary of the available information on production, presence, potential hazards to human health and environment, and release and behaviour of metal-based ENPs in surface waters and drinking water. In addition, the most extensively studied water treatment processes to remove metal-based ENPs, specifically conventional and advanced processes, are discussed and highlighted in detail. Furthermore, this work identifies the research gaps regarding ENPs removal in DWTPs and discusses future aspects of ENPs in water treatment.